Characteristics of Oral Mucosal Lesions and Their Association With Socioeconomic Status and Systemic Health: A Cross-Sectional Study of Consecutively Collected Oral Medicine Clinic Data in a Remote Rural Area of China - Yao, Hui; Zhang, Qiongyue; Song, Qianqian; Liu, Mingshan; Tang, Guoyao (Frontiers in Public Health, 2022)
Objectives Epidemiological data of oral mucosal lesions (OMLs) are required to develop practical oral care policies. However, limited data are available for rural areas in China. We aimed to estimate the spectrum and frequency of OMLs and to identify their associated socioeconomic status (SES) and systemic health in a remote rural area in Yunnan, China. Methods We screened patients for OMLs in an oral medicine clinic in rural Yunnan, China, from August 2020 to February 2021. OMLs were documented. SES, including the highest education level achieved and the previous month's household income, as well as the patient's systemic health, including a history of smoking, alcohol use, and chronic disease, were obtained from the Medical History/Health Questionnaire Form and patient medical records. Results A total of 146 patients were found to have OMLs. The most frequent OML was aphthous ulcer (n = 41, 28.1%), followed by burning mouth syndrome (BMS) (n = 16, 11.0%), viral ulcer (n = 14, 9.6%), and oral lichen planus (OLP) (n = 9, 6.2%). In these patients, the most common chronic diseases were sleep apnea (n = 35, 24.0%), hypertension (n = 23, 15.8%), bronchitis (n = 16, 11.0%), reflux (including gastroesophageal reflux disease) (n = 12, 8.2%), and arthritis (n = 11, 7.5%). On adjusted regression, the patients without chronic diseases had a lower risk of BMS than those with chronic diseases [odds ratio (OR), 0.2; 95% confidence interval (CI), 0.03–0.9]. Age was an independent protective factor for viral ulcers (OR, 1.0; 95% CI, 0.9–1.0). Patients with low-income levels had a lower risk of OLP than those with high-income levels (OR, 0.2; 95% CI, 0.05–0.9). Conclusions Our oral medicine clinic data in remote Yunnan, China, showed the most frequent OML was aphthous ulcer, which was followed by BMS, viral ulcer, and OLP. Oral care policies should be prioritized among patients with aphthous ulcer. Preventive strategy of BMS should be targeted to people with chronic disease for health equalities. Therefore, an individualized strategy for interventions of OMLs might be optimal, based on the specific epidemiologic characteristics in rural settings.